KORELASI SELF-EFFICACY TERHADAP HASIL BELAJAR IPA PESERTA DIDIK DALAM PEMBELAJARAN ONLINE - Firdausy, Nanda; Sirait, Judyanto; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
A few years ago, learning was carried out online. This also affects students' beliefs, strategies and learning outcomes in science. Factors originating from within students that influence learning outcomes are one of the characteristics that show self-efficacy, namely self-confidence in the abilities possessed. This research method uses annassociative method with a type of quantitative research that aimsnto clarify thencorrelation betweennself-efficacy withnscience learningnoutcomes. This research was conducted by describing how big thecorrelation is self-efficacynwithnlearning outcomes that are implemented in science subjects. The sampling technique of this study uses the technique probability samplingntype cluster random sampling and obtained a sample of 60 students. Data analysis this using correlation test PearsonnProductnMoment.nThe conclusion ofnthisnstudy, selfefficacy positively and significantly correlated with students' science learning outcomes in learning online in class VIII SMP Negeri 9 by contributing 60.3% and the remaining 39.6% was influenced by other variables notnincludednin this study